Targeted immunomodulation therapy for cardiac repair by platelet membrane engineering extracellular vesicles via hitching peripheral monocytes. (May 2022) - Li, Qiyu; Huang, Zheyong; Wang, Qiaozi; Gao, Jinfeng; Chen, Jing; Tan, Haipeng; Li, Su; Wang, Zhengmin; Weng, Xueyi; Yang, Hongbo; Pang, Zhiqing; Song, Yanan; et al.
Abstract: Immune regulation therapies have been considered promising in the treatment of myocardial ischemia reperfusion (MI/R) injury. Mesenchymal stem cells derived extracellular vesicles (MSC-EVs) are of great potential for immune modulation by reprogramming macrophages but their therapeutic efficacy is hindered by insufficient targeting ability in vivo . Herein, we introduced the platelet membrane modified EVs (P-EVs) based on membrane fusion method to mimic the binding ability of platelets to monocytes. In the mouse model of MI/R injury, the intravenously injected P-EVs were mainly carried by circulating monocytes into the ischemic myocardium. In the inflammatory microenvironment, those monocytes subsequently differentiated into macrophages with enhanced phagocytosis, which probably promoted in-situ endocytosis of the superficial P-EVs by monocytes differentiated macrophages in large quantities. Then, the P-EVs successfully escaped from the macrophage lysosome and released the functional microRNAs (miRNAs) into the cytosol which facilitated the inflammatory macrophages (M1 phenotype) reprogramming to reparative macrophages (M2 phenotype). Finally, the immune microenvironment was regulated to realize cardiac repair. Thus, we supposed that the most likely delivery method was that monocytes mediated P-EVs migration into ischemic myocardium where P-EVs were mainly in-situ endocytosed by monocytes derived macrophages, which holds potential for immunoregulation on MI/R and other immune-related diseases in the future.